2010
DOI: 10.1116/1.3244575
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dopant profiling of p-n junction in InGaAs∕AlGaAs light-emitting diode using off-axis electron holography

Abstract: The electrostatic potential profile across the p-n junction of an InGaAs light-emitting diode with linearly graded AlGaAs triangular barriers has been measured using off-axis electron holography. Simulations of the junction profile show small discrepancies with experimental measurements in the region of the p-and n-doped AlGaAs barriers, which are located away from the InGaAs quantum wells. Revised simulations reproduce the measurements reasonably when a carrier-trap density of 6 ϫ 10 16 cm −3 in the AlGaAs ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Two of the most common holographic techniques are off-axis EH and bright field through focus in-line EH. Both of these techniques have widely been used to characterize homogeneous and monocrystalline material systems, such as silicon-based devices (e.g., [11][12][13][14][15][16]), nitrides (e.g., [17,18]), GaAs systems (e.g., [19]), single nanoparticles (e.g., [20][21][22]), or simple interfaces (e.g., [23][24][25][26]). However, only few EH studies have been reported on more complex materials, such as the CIGS compound (e.g., [6,27,28]).…”
Section: +mentioning
confidence: 99%
“…Two of the most common holographic techniques are off-axis EH and bright field through focus in-line EH. Both of these techniques have widely been used to characterize homogeneous and monocrystalline material systems, such as silicon-based devices (e.g., [11][12][13][14][15][16]), nitrides (e.g., [17,18]), GaAs systems (e.g., [19]), single nanoparticles (e.g., [20][21][22]), or simple interfaces (e.g., [23][24][25][26]). However, only few EH studies have been reported on more complex materials, such as the CIGS compound (e.g., [6,27,28]).…”
Section: +mentioning
confidence: 99%